Integrating IoT Into Project-Based Learning: A New Approach to Teaching Indonesian Language and Promoting Computational Thinking - Fauziah Nasution; Fita Delia Gultom; Khairunnisa Samosir; Eni Sumanti Nasution; Albert Efendi Pohan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This research pioneers the development of Project-Based Learning (PjBL) Indonesian Language teaching materials integrated with the Internet of Things (IoT) to enhance literacy and computational thinking skills among Grade VII students of SMP Negeri 5 Padangsidimpuan. The innovative integration of IoT in PjBL offers a novel approach to language learning, enabling students to engage with real-world problems and develop essential skills for the digital age. The study aims to determine the effectiveness of the developed materials, assess students' responses to the implementation of IoT-integrated PjBL, and evaluate the improvement in literacy and computational thinking skills. Using the ADDIE model, the research involves analysis, design, development, implementation, and evaluation phases. The developed materials have been deemed "Very Good" and are considered a viable alternative learning resource for students and teachers. The findings of this research are expected to serve as a reference for future applied research and inspire further development of the learning materials for mass production and widespread adoption in middle schools.